Genitourinary radiology: Kidney, bladder and urethra the pathologic basis - Dogra, Vikram S.; MacLennan, Gregory T.; Turgut, Ahmet Tuncay; Canacci, Anastasia; Onur, Mehmet Ruhi (Springer-Verlag London Ltd, 2013)
Genitourinary Radiology: Kidney, Bladder and Urethra: The Pathologic Basis provides a lavishly illustrated guide to the radiologic and pathologic features of a broad spectrum of genitourinary diseases of the urinary tract, including the entities most commonly encountered in day to day practice. The editors are authorities in the fields of genitourinary radiology and pathology, and the authors of each chapter are renowned radiologists. The pathology content of the chapters has been provided by an internationally recognized genitourinary pathologist. Genitourinary Radiology: Kidney, Bladder and Urethra: The Pathologic Basis covers inflammatory conditions, vascular disorders and cystic disease of the kidney; neoplasms of the kidney, renal pelvis, bladder and urethra; non-neoplastic disorders of the renal pelvis, bladder and urethra; kidney and bladder trauma; calculus disease; and medical renal disease. General, plain film, intravenous pyelography, ultrasound, computed tomography, magnetic resonance imaging, nuclear medicine imaging and PET imaging of each disease entity are included. Accompanying the majority of the radiological narratives are complementary descriptions of the gross and microscopic features of the disease entities. Genitourinary Radiology: Kidney, Bladder and Urethra: The Pathologic Basis is aimed at radiologists in private and academic practice, radiology residents, urologists, urology trainees, pathology trainees and fellows specializing in genitourinary pathology. Both experts and beginners can use this excellent reference book to enhance their skills in the fields of genitourinary radiology and pathology. © Springer-Verlag London 2013.